Aceruloplasminemia: A Severe Neurodegenerative Disorder Deserving an Early Diagnosis - Marchi, Giacomo; Busti, Fabiana; Lira Zidanes, Acaynne; Castagna, Annalisa; Girelli, Domenico (Frontiers in Neuroscience, 2019)
Aceruloplasminemia (ACP) is a rare, adult-onset, autosomal recessive disorder, characterized by systemic iron overload due to mutations in the Ceruloplasmin gene (CP), which in turn lead to absence or strong reduction of CP activity. CP is a ferroxidase that plays a key role in iron export from various cells, especially in the brain, where it maintains the appropriate iron homeostasis with neuroprotective effects. Brain iron accumulation makes ACP unique among systemic iron overload syndromes, e.g., various types of genetic hemochromatosis. The main clinical features of fully expressed ACP include diabetes, retinopathy, liver disease, and progressive neurological symptoms reflecting iron deposition in target organs. However, biochemical signs of the disease, namely a mild anemia mimicking iron deficiency anemia because of microcytosis and low transferrin saturation, but with “paradoxical” hyperferritinemia, usually precedes the onset of clinical symptoms of many years and sometimes decades. Prompt diagnosis and therapy are crucial to prevent neurological complications of the disease, as they are usually irreversible once established. In this mini-review we discuss some major issues about this rare disorder, pointing out the early clues to the right diagnosis, instrumental to reduce significant disability burden of affected patients.